Effect of Masonry Infill Panels on the Seismic Response of Reinforced Concrete Frame Structures - Zine, Ali; Kadid, Abdelkrim; Zatar, Abdallah (Civil Engineering Journal, 2021)
The present work concerns the numerical investigation of reinforced concrete frame buildings containing masonry infill panel under seismic loading that are widely used even in high seismicity areas. In seismic zones, these frames with masonry infill panels are generally considered as higher earthquake risk buildings. As a result there is a growing need to evaluate their level of seismic performance. The numerical modelling of infilled frames structures is a complex task, as they exhibit highly nonlinear inelastic behaviour, due to the interaction of the masonry infill panel and the surrounding frame. The available modelling approaches for masonry infill can be grouped into two principal types; Micro models and Macro models. A two dimensional model of the structure is used to carry out non-linear static analysis. Beams and columns are modelled as non-linear with lumped plasticity where the hinges are concentrated at both ends of the beams and the columns. This study is based on structures with design and detailing characteristics typical of Algerian construction model. In this regard, a non-linear pushover analysis has been conducted on three considered structures, of two, four and eight stories. Each structure is analysed as a bare frame and with two different infill configurations (totally infilled, and partially infilled). The main results that can be obtained from a pushover analysis are the capacity curves and the distribution of plastic hinges in structures. The addition of infill walls results in an increase in both the rigidity and strength of the structures. The results indicate that the presence of non-structural masonry infills can significantly modify the seismic response of reinforced concrete "frames". The initial rigidity and strength of the fully filled frame are considerably improved and the patterns of the hinges are influenced by structural elements type depending on the dynamic characteristics of the structures.Â Doi: 10.28991/cej-2021-03091764 Full Text: PDF